Review of the book Los Niños del Perú - Canqui Santiago, Glenn Alexander (2020)
The work of the sociologist Carlos Castillo Ríos allows us to enter the world of children in Peru, but from a political-economic perspective. This review seeks to revalue the arguments that the author maintains about the influence of the capitalist system on the development and training of children. Through a study on the characteristics of the children of each social class that is made in the chapters of the work, the criticism of the capitalist system that generates so much inequality from the foundations of a society, which are children, is sustained.